Interference periods of sourgrass (Digitaria insularis) on maize crop - Piazentine, Ana E. [UNESP]; Martins, Heytor L. [UNESP]; Rodrigues, Juliana de S. [UNESP]; Carrega, Willians C. [UNESP]; Alves, Pedro L.C.A. [UNESP] (Southern Cross Publishing, 2024)
Sourgrass (Digitaria insularis (L.) Fedde) is frequently reported as one of the main weeds in grain production, along with several reports of herbicide resistance. The objectives of this study were (1) to understand the length of time that the maize crop, cv. P4285VYHR PIONEER could coexist with a weed community dominated by D. insularis plants without suffering any negative impact on its final production, and (2) the period for which the crop needs to be free of this interference to ensure optimal production. The periods of weed interference and/or control were: 15, 30, 45, 60, 75, 90, 105, and 130 days after sowing maiz, to determine the period before interference (PBI), the total period of interference prevention (TPIP), and the critical period of weed interference (CPWI). A weed community predominantly containing D. insularis coexisting with the maize crop decreases yield by up to 86%, reduces plant height, the insertion height of the first ear, and the weight of 1000 grains. Maize can coexist with such a community (PBI) for 30 DAS, tolerating yield losses of up to 5%, without TPIP and, consequently, CPWI.
Keywords: Coexistence; Digitaria insularis (L.) Fedde; PAI; weeds; Zea mays L